Perilaku Konsumen Mobile Internet dalam Penggunaan Paket Layanan Unlimited - Hurriyati, Dwi; Arisandy, Desy (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2019)
.Indonesia is the most active country in using social media. Indonesia is also the largest online market with the fastest growth in Southeast Asia. This has caused many adult mobile internet users to purchase service packages that are considered satisfactory in terms of both quantity and quality. The phenomenon of internet growth and adult mobile internet users in Indonesia is certainly a potential target of telecommunications operators in marketing products in accordance with the wishes of consumers. The population in this study is consumers of mobile users who are equipped with modems for the internet (mobile internet) aged 18-40 years, especially who bought the unlimited Smartfren service package in Palembang. The sampling technique used was accidental sampling. The measuring instrument used in the form of a scale of mobile internet consumer behavior and purchasing decisions. The analysis technique used is quantitative analysis using simple regression analysis (simple regression) with SPSS Version 20 for Windows aids. Based on the results of data analysis, it is known that the correlation coefficient between mobile internet consumer behavior and purchasing decisions is r = 0.846 with p = 0.000 where p â‰¤ 0.01. Thus, the hypothesis which states that there is a relationship between consumer behavior of mobile internet with the decision to purchase unlimited smartfren service packages in Palembang is proven. Thus, there is a very significant relationship between the behavior of consumers of mobile internet with the decision to purchase an unlimited smartfren service package in Palembang.